THE EFFECT OF CARD SORT IN TEACHING WRITING - Yuliarsih, Yuli; Anjarani, Devie Reztia (The Ellite of Unira, 2024)
Writing is one of important skill in language learning, which needs extra attention to be mastery and desired proficiency. In fact, this skill is still minimally touched, especially for teaching writing using media.Thisstudy is aimed to find the effectiveness using card sort as media in teaching writing at SMP Maarif 10 Pamekasan. Card sort is alternative media for assist students in teaching writing. This research method is a quasi-experimental design with Nonequivalent Control Group Design. The results found that in the experimental class the proportion score was higher than in the control class. There is a significant effect of the use of card sort as media in teaching writing. It can be concluded that there is a difference in the average score of students’ writing ability scores between teacher teaches writing with card sort and teacher teaches writing without card sort. The main thing is increasing students writing skills because writing paragraph using card sort media can attract students’ enthusiasm for learning.